1978
DOI: 10.1007/bf01477459
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypokalemic nephropathy: A clinical study

Abstract: Description of 23 patients (21 women, 2 men) with an average age of 36.6 (19--68) years, who were hypokalemic during 6.5 years on the average (range 1/2--16 years). The cause of the potassium depletion was malnutrition (anorexia nervosa, vomiting) and/or abuse of laxatives and/or diuretics. With increasing duration of potassium depletion renal function deteriorated; in two cases terminal renal failure developed. Histology of the kidneys (9 cases) showed the picture of chronic abacterial interstitial nephritis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
3
19
1
Order By: Relevance
“…Pere et al (29,30) reported that a high-potassium diet (2.4% potassium) is renoprotective in cyclosporine-induced nephrotoxicity, compared with a diet containing 0.8% potassium. In contrast, chronic potassium depletion causes renal functional deterioration, interstitial nephritis, or cyst formation in animals and humans (3,4,6,11,32,34,40,47). The proposed underlying mechanisms of the deleterious effect of potassium depletion include activation of the local renin-angiotensin II system (RAS) (32), increased angiotensin II receptor (AT 1 ) expression (12), and altered activity of the sodium-potassium pump in the renal tubule (35), acting by blood pressure-dependent and/or blood pressureindependent mechanisms.…”
mentioning
confidence: 99%
“…Pere et al (29,30) reported that a high-potassium diet (2.4% potassium) is renoprotective in cyclosporine-induced nephrotoxicity, compared with a diet containing 0.8% potassium. In contrast, chronic potassium depletion causes renal functional deterioration, interstitial nephritis, or cyst formation in animals and humans (3,4,6,11,32,34,40,47). The proposed underlying mechanisms of the deleterious effect of potassium depletion include activation of the local renin-angiotensin II system (RAS) (32), increased angiotensin II receptor (AT 1 ) expression (12), and altered activity of the sodium-potassium pump in the renal tubule (35), acting by blood pressure-dependent and/or blood pressureindependent mechanisms.…”
mentioning
confidence: 99%
“…Renal insufficiency in eating disorders has been reported to be induced by hypokalemia relevant to vomiting or laxative abuse (Bock et al, 1978;Copeland, 1994;Ishikawa et al, 1999;Riemenschneider & Bohle, 1983;Tsuchiya et al, 1995). The initial biopsy (1977) showed juxtaglomerular hyperplasia, and repeated biopsy (2001) showed interstitial nephritis and proximal tubular swelling.…”
Section: Resultsmentioning
confidence: 94%
“…However, few studies have revealed the extent of renal damage, especially morphologic changes, over long-term bulimic symptoms (Bock et al, 1978;Copeland, 1994;Riemenschneider & Bohle, 1983;Tsuchiya et al, 1995). To our knowledge, this is the first case report of a patient with longstanding bulimia nervosa and an eventual ''end-stage kidney'' characterized by hypokalemic nephropathy and diffuse glomerulosclerosis.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hypokalemia and chronic dehydration, caused by laxative and/or diuretic abuse and chronic fluid restriction, appear to be the most likely mechanisms for the development of these conditions. Bock, Cremer, and Werner (1978) reported on a series of 23 patients with chronic hypokalemia, renal insufficiency, and eating disorders, showing secondary interstitial nephritis in the 9 patients for whom biopsy material was available. Low protein intake may play a role by causing a decrease in the glomerular filtration rate (GFR; Ichikawa, Purkerson, & Klahr, 1980).…”
Section: Resultsmentioning
confidence: 98%